PEMILIHAN MODA TRANSPORTASI OLEH MAHASISWA MENUJU KAMPUS 1 UNIVERSITAS PGRI SEMARANG - Imawan, Heggy; Rizani, Mohammad Debby; Ariawan, Donny (Universitas PGRI Semarang, 2024)
Transportation activities themselves require facilities and infrastructure to be used by the community in carrying out transfer activities to their destination. Congestion is a transportation problem caused by the increasing volume of motorized vehicles without being matched by road capacity. The choice of transportation mode is a separate reason for each person and will reflect the interest of one of the modes of transportation itself. Data collection used an online questionnaire, namely via the Google form which was distributed randomly to students studying at Campus 1 Universitas PGRI Semarang. And data processing of travellers was analyzed using descriptive statistics, and vehicle modes were analyzed using a binary difference logit model with the help of multiple linear regression equations. And produce student profile data that has been obtained, that the dominant student is from the FTI faculty, the dominant one is traveling, namely semester 4. The sex is dominated by male, the dominant mode of vehicle used is motorcycle, and the dominant driver's license is SIM C. Characteristics of ability found that students travel based on the amount of pocket money, expenses or vehicle operations and considerations for traveling.